Analysis of Factors Affecting Public Interest to Register for a Motor Vehicle Insurance Program - Julian Azhar; Muhammad Akbar F; Septian Nugraha (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
This research aims to determine the factors that influence public interest in registering for a motor vehicle insurance program. This research was conducted using a descriptive design or method with a qualitative model. The subjects in this research were motor vehicle insurance products provided by several insurance companies in Indonesia such as Allianz Utama Indonesia, Adira Autocillin, and Sinar Mas. The object of this research is the factors that influence people's interest to become customers in the motor vehicle insurance program. The data were collected using the literature study method and analyzed by comparing the facts or social phenomena that occurred with the theory that have been put forward by experts and of similar previous articles. The results showed that the factors influencing public interest in registering for the motor vehicle insurance program consisted of internal factors (income factors, education factors, job factors, and gender factors) and external factors (reputation of product factors, promotion factors, premium price factors, and reference/ recommendation factors).